Effects of interval training of maximal effort intensity - Norkowski, H.; Kuder, A.; Hucinski, T.; Przybylski, S. (Baltic Journal of Health and Physical Activity, 2010)
Background: The purpose of this study was to determine changes in anaerobic capacity at 100% physical effort intensity in the examined people.